Pemanfaatan Media Pembelajaran Berbasis Video Menggunakan Aplikasi Benime dalam Meningkatkan Pemahaman pada Mata Pelajaran Pendidikan Agama Islam dan Budi Pekerti (PAIBP) Siswa SMP - Ulvia Nur Aini; Tri Wardah Utami; Tuhfatul Khalidiyah; Lilik Huriyah (Institut Agama Islam Negeri Kediri, 2022)
Abstract: Video learning media is a media that combines two elements, namely audio and visual (image). Benime application is an application that produces videos with attractive and not monotonous illustrations. The hope of using the media is that students can be more effective in understanding the material presented. This study aims to develop video media using the benime application and measure the effectiveness of learning videos using the benime application in improving understanding of the material